Records Reformed and Reused. Nostalgic and Ecological Concerns in Contemporary Media Art - Kelly, Caleb (Revue musicale OICRM, 2023)
In the twentieth century, records and record players were employed as the media and medium of art and music. These generative practices sought to extend the possibilities for sound production, at times ending in the destruction of both vinyl and turntable—what I call cracked media. This paper will revisit cracked media in the twenty-first century, inquiring into how this (re)interest in vinyl has translated into art and music. I will look to contemporary musicians and artists to contrast practices that encapsulate nostalgia with those that seek to communicate ecological and environmental concerns.